(Cover; from the editor; Editorial Team; Table of Contents) - (Cover; from the editor; Editorial Team; Table of Contents) (FITOFARMAKA: Jurnal Ilmiah Farmasi, 2020)
1. Cover2. from the editor3. Editorial Team4. Table of Contents